A three-modal epitaxial adsorption of formamide (HO–C–NH2) on the {111} surfaces of f.c.c. alkali halide crystals growing from aqueous solutions. Issue 47 (15th November 2016) - Pastero, L.; Aquilano, D.
Abstract : The whole series of the face-centered cubic (f.c.c.) alkali halides, from to LiF to RbI, has been crystallized from aqueous solutions in the presence of variable amounts of formamide (HO–C–NH2 ). Abstract : The whole series of the face-centered cubic (f.c.c.) alkali halides, from LiF to RbI, has been crystallized from aqueous solutions in the presence of variable amounts of formamide (HO–C–NH2 ). Scanning electron microscope images show that the corresponding morphology of the grown crystals is not homogeneous within the whole crystal series, and that the {111} octahedron does appear and compete with the {100} cube only in three separated crystal domains: (NaF), (LiBr, RbF, NaCl) and (KCl, NaI, RbCl, KBr). Starting from our preceding finding about the formation of NaCl/formamide anomalous mixed crystals and recollecting the peculiar {100} + {111} habit change of NaCl growing from pure aqueous solution, we propose that formamide can be adsorbed as a 2D epitaxial layer on the {111} surfaces of the f.c.c. alkali halides according to a three-modal distribution.